Periodontal disease in a patient with Prader-Willi syndrome: a case report - Yanagita, Manabu (BioMed Central, 2011)
INTRODUCTION: Prader-Willi syndrome is a complex genetic disease caused by lack of expression of paternally inherited genes on chromosome 15q11-q13. The prevalence of Prader-Willi syndrome is estimated to be one in 10,000 to 25,000. However, descriptions of the oral and dental phenotype are rare. CASE PRESENTATION: We describe the clinical presentation and periodontal findings in a 20-year-old Japanese man with previously diagnosed Prader-Willi syndrome. Clinical and radiographic findings confirmed the diagnosis of periodontitis. The most striking oral findings were anterior open bite, and crowding and attrition of the lower first molars. Periodontal treatment consisted of tooth-brushing instruction and scaling. Home care involved recommended use of adjunctive chlorhexidine gel for tooth brushing twice a week and chlorhexidine mouthwash twice daily. Gingival swelling improved, but further treatment will be required and our patient's oral hygiene remains poor. The present treatment of tooth-brushing instruction and scaling every three weeks therefore only represents a temporary solution. CONCLUSIONS: Rather than being a direct result of genetic defects, periodontal diseases in Prader-Willi syndrome may largely result from a loss of cuspid guidance leading to traumatic occlusion, which in turn leads to the development of periodontal diseases and dental plaque because of poor oral hygiene. These could be avoided by early interventions to improve occlusion and regular follow-up to monitor oral hygiene. This report emphasizes the importance of long-term follow-up of oral health care by dental practitioners, especially pediatric dentists, to prevent periodontal disease and dental caries in patients with Prader-Willi syndrome, who appear to have problems maintaining their own oral health.